Plasma Leptin Concentrations and Esophageal Hypomotility in Obese Patients - Justin Côté-Daigneault; Pierre Poitras; Rémi Rabasa-Lhoret; Mickael Bouin (Canadian Journal of Gastroenterology and Hepatology)
BACKGROUND: Although esophageal hypomotility is prevalent in obese patients, its cause remains unknown. Leptin, a hormone derived from adipose tissue, may be involved in this phenomenon because it has been shown to decrease gastric and intestinal motility in animals. It has been hypothesized that elevated plasma leptin concentration is a risk factor for esophageal dysmotility in obese patients.